2013
DOI: 10.3390/vaccines1030278
|View full text |Cite
|
Sign up to set email alerts
|

Innate Immune Signaling by, and Genetic Adjuvants for DNA Vaccination

Abstract: DNA vaccines can induce both humoral and cellular immune responses. Although some DNA vaccines are already licensed for infectious diseases in animals, they are not licensed for human use because the risk and benefit of DNA vaccines is still controversial. Indeed, in humans, the immunogenicity of DNA vaccines is lower than that of other traditional vaccines. To develop the use of DNA vaccines in the clinic, various approaches are in progress to enhance or improve the immunogenicity of DNA vaccines. Recent stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(33 citation statements)
references
References 80 publications
0
30
0
3
Order By: Relevance
“…In most cases, the recognition of cytosolic DNA results in the induction of the innate immune response through the STING-TBK1 signaling cascade, and thus the subsequent expression of type I IFNs. 13 These cytokines play a crucial role in the induction of a protective antitumor immune response. 21 Adjuvant properties of EP had already been highlighted previously in a series of studies, showing its capacity to trigger a 100-fold increase of antigen expression 7 but also to recruit DCs to the vaccinated area and induce local tissue inflammation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In most cases, the recognition of cytosolic DNA results in the induction of the innate immune response through the STING-TBK1 signaling cascade, and thus the subsequent expression of type I IFNs. 13 These cytokines play a crucial role in the induction of a protective antitumor immune response. 21 Adjuvant properties of EP had already been highlighted previously in a series of studies, showing its capacity to trigger a 100-fold increase of antigen expression 7 but also to recruit DCs to the vaccinated area and induce local tissue inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…11 These genetic adjuvants include cytokines, chemokines, or immune stimulatory molecules, such as toll-like receptor (TLR) agonists or interferon (IFN) regulatory factors. 7,[12][13][14] Most of these adjuvants are used in preclinical studies, and even though they are promising, only a few of them have been evaluated in clinical trials until now. Therefore, there is still a critical need of clinically applicable genetic adjuvants.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, general criteria have been proposed for assessing the efficacy of decellularization, including the quantitative measurement of DNA of less than 50 ng/mg dry tissue and fragment sizes below 200 bp (Gilbert 2012); these authors ensure that DNA fragments of less than 300 bp in length are likely too short to be of concern, but other reports indicate that even a 25 bp DNA can elicit an immunological response (Kobiyama et al 2013). They also concluded that more thorough methods of tissue decellularization would be desirable and any quality assurance steps that guarantee the absence of cell remnants would be welcome.…”
Section: Discussionmentioning
confidence: 99%
“…One of the primary advantages of DNA vaccination is the “built-in” adjuvant effect, or the ability of bacterial DNA to itself stimulate innate immune responses (Kobiyama et al, 2013). Mammalian cells have evolved to sequester DNA within the nuclear compartment and its presence in the cytoplasm is sufficient to activate several innate immune signaling cascades (Barber, 2011; Nie & Wang, 2013; Sharma & Fitzgerald, 2011).…”
Section: Dna Vaccines – Mechanisms Of Action; Increasing Immunogenmentioning
confidence: 99%